Associations of high‐resolution‐typing‐defined MICA and MICB polymorphisms, and the levels of soluble MICA and MICB with Oral Squamous Cell Carcinoma in Bulgarian patients. (26th April 2021) - Ivanova, Milena; Al Hadra, Bushra; Yordanov, Stanislav; Lesichkova, Spaska; Stoyanov, Hristo; Shivarov, Velizar; Deliverska, Elitsa
Abstract: Background: Oral Squamous Cell Carcinoma (OSCC) is a malignancy characterized by an aggressive tumor growth and significant mortality. Clarifying mechanisms responsible for immunomodulation are among the main challenges for the development of personalized approaches for the management of patients with Oral Squamous Cell Carcinoma. The aim of the present study was to analyze the relevance of MICA and MICB to Oral Squamous Cell Carcinoma pathogenesis focusing on allele polymorphisms and the levels of soluble MICA and MICB molecules. Materials and methods: 73 patients diagnosed with Oral Squamous Cell Carcinoma and 149 healthy controls from the Bulgarian population were included in the study. MICA and MICB polymorphism was analyzed at high‐resolution level using Next‐Generation Sequencing. Serum levels of soluble MICA and MICB molecules were measured by ELISA. Results: Our results show significant protective association with MICB*002:01, while relatively rare alleles MICB*018, *019, and *020 were observed with statistically significant increased frequency in Oral Squamous Cell Carcinoma patients compared to controls. Additionally, a predisposing association was observed for MICA*008:01‐MICB*019 haplotype. A correlation analysis between functionally relevant MICA polymorphisms and sMICA showed that homozygosity for MICA‐A5.1 or 129Val in OSCC patients was associated with significantly higher serum levels of sMICA. Conclusion: This is the first study showing significant associations between MICB alleles and Oral Squamous Cell Carcinoma and suggesting the possible role of MICB in immunosurveillance in Oral Squamous Cell Carcinoma development. Observed correlations between the levels of soluble MICA molecules and functionally relevant polymorphisms might represent a further step toward a better understanding of molecular mechanisms of Oral Squamous Cell Carcinoma and developing strategies for therapeutic targeting harnessing effective immunosurveillance.